2012
DOI: 10.2304/plat.2012.11.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mindful Awareness Practices on College Student Health, Well-Being, and Capacity for Learning: A Pilot Study

Abstract: This preliminary study examined the feasibility and potential utility of mindful awareness practices (MAPs) in terms of enhancing student learning in the college classroom, as well as improving psychological well-being. One of two identical undergraduate psychology sections included a 10-minute MAP at the beginning of every class (mindfulness group n = 37; control group n = 23). Primary learning and secondary self-report outcomes were obtained. Controlling for significant demographic covariates, students in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 23 publications
4
44
1
2
Order By: Relevance
“…This finding aligns with many studies reporting the positive effects of contemplative practices on student learning (Arnold, 2011;Franco et al, 2010;Ramsburg & Youmans, 2014;Schlesiger, 1995) but contrasts with results of a prior study (Yamada & Victor, 2012) that found no improvements in student grades. Previous research (e.g., Hjeltnes et al, 2015;Jha et al, 2007;Zeidan et al, 2010) has shown that contemplative practices enhance focus, attention, concentration, and processing, resulting in improved learning and performance.…”
Section: Discussionsupporting
confidence: 82%
“…This finding aligns with many studies reporting the positive effects of contemplative practices on student learning (Arnold, 2011;Franco et al, 2010;Ramsburg & Youmans, 2014;Schlesiger, 1995) but contrasts with results of a prior study (Yamada & Victor, 2012) that found no improvements in student grades. Previous research (e.g., Hjeltnes et al, 2015;Jha et al, 2007;Zeidan et al, 2010) has shown that contemplative practices enhance focus, attention, concentration, and processing, resulting in improved learning and performance.…”
Section: Discussionsupporting
confidence: 82%
“…As a component of larger behavioral interventions, MM produces symptom reduction and improved QOL for individuals suffering from anxiety disorders (e.g., Chen et al, 2012;Khoury et al, 2013;Serpa, Taylor, & Tillisch, 2014). Brief mindfulness training helps individuals learn how to regulate negative responses to stimuli, and even infrequently practiced MM increases well-being and reduces worry, general anxiety symptoms, and psychological distress for people with mild anxiety symptoms (Call, Miron, & Orcutt, 2014;Cavanagh et al, 2013;Delgado-Pastor et al, 2015;Vesa, Liedberg, & Rönnlund, 2016;Yamada & Victor, 2012). However, mindfulness-based treatments are not always successful, particularly when anxiety symptom reduction is the desired outcome (Strauss, Cavanagh, Oliver, & Pettman, 2014).…”
Section: Mindfulnessmentioning
confidence: 99%
“…Along with attending to norms for interaction, I (the second author) attend to students' experience in the class through the practice of mindfulness. While mindfulness has been associated with psychological well-being and stress reduction outside of the classroom, there is also evidence that mindfulness has similar benefits if practiced in a learning environment [18]. I came to higher education from a career in mental health treatment; after my positive experiences using mindfulness in a treatment setting, I adapted the mindfulness practice for the classroom.…”
Section: Mindfulnessmentioning
confidence: 99%